EFEKTIFITAS TEKNIS DAN EFEKTIFITAS PELAYANAN PELAKSANAAN PUBLIC SERVICE OBLIGATION (PSO) KERETA API KELAS EKONOMI ANGKUTAN PERKOTAAN - P Pradono; Miming Miharja; Amanda Pritasari; A Adriani (TATALOKA, 2013)
Public Service Obligation (PSO) is government's obligation to provide affordable price and to optimize service in typicaly economy class of urban railway commuting. It is therefore important to evaluate its technical and service effectiveness. This article aims to assess the effectiveness of PSO railway services in economy class of urban railway, in accordance with the initial goals of PSO implementation. Using Data Envelopment Analysis (DEA) tool, technical effectiveness analysis is carried out by comparing the input (operating expenses, number of facilities, and amount of PSO) and output (and revenue passenger kilometers). Services Effectiveness is aimed to determine the effectiveness of service of two inputs that are train kilometers and kilometer of seats by comparing the 2 output namely kilometers passengers and revenue. The results show that only 4 out of 12 DMU have maximum level of technical effectiveness, and   only 3 out of 12 DMUs are having effective service.